‘Shiv Khori’ – A Case of An Antecedents Destination Planning Management - Mangoch, Sourav (The journal of contemporary issues in business and government, 2020)
Pilgrimage Tourism must have potential locations and customer centers, which could be developed for tourism activities and one such place is “Shiv Khori”. The case is written with a feeling that it is more necessary to revive and enlarge the existing sites of tourist interest, develop an interdependence of the local population with the developmental activity and allow the absorption of the overflows of such economic activity to benefit the local population and only then consider moving in identified new areas. It was also realized that the increasing population pressure requires the local population to be first moved into areas which are rich in tourist potential and in their rehabilitation the infrastructure of new tourist and small trade activities would need to be incorporated. Need is also to explore the potential places to be highlighted as tourist points for economic wellbeing.